Design of a Flexible and Adaptable LMS Engine in Conformance with PoEML - Pérez-Rodríguez, Roberto; Caeiro-Rodriguez, Manuel; Anido-Rifon, Luis (International Journal of Emerging Technologies in Learning (iJET), 2009)
This paper describes the support of the Structural, Functional, Order and Temporal perspectives in PoEML. PoEML is a modeling language devoted to support a broad range of pedagogical approaches, from content-based, to collaborative and practical oriented. At this point, a main issue is to provide a good level of adaptability and flexibility. The final goal is to support changes in the educational process development, enabling the provision of different learning experiences depending on the learning goals, the learner needs and features, the previous results, etc. The introduced solution is based on the separation of concerns principle adopted in PoEML. Basically, the solution facilitates the use of a set of educational resources in different ways by separating the form in which such resources are organized (Structural perspective) from the decisions of what has to be done (Functional perspective) and when (Order and Temporal perspectives).